Strominge in die vrouebew eging: 'n voorlopige raamwerk - Niekerk, M. van (Koers, 1988)
The Biblical principle of reformation challenges the Christian to question the traditional position of women and if necessary to change it, as well as to critically evaluate the various trends within the women's movement. It is stated that the generalizing use of the term feminism has become outdated, and should be replaced by differentiated terminology. The latter should be based on critical nuancing, with due regard to the view of history, the approach to sexuality/sex and the religious directedness of each specific trend or school of thought. Against the background of the sexism and traditionalism of male chauvinism , this article offers a prelim inary framework from which a number of fem inist and moderate trends within the women's movement can be identified. Within feminism a distinction is drawn between egalitarian and gynaecentric (neo-sexist) trends. The moderate wing of the women's movement includes a humanist and a Christian approach, with androgynous and holistic views respectively as examples of these. Finally the author points out that the use of the Bible by feminist theologians and other representatives of the women's movement offers no guarantee for Scriptural viewpoints, and warns against generalizing judgments about proponents of women's rights.